Beyond THC: The New Generation of Cannabinoid Designer Drugs - Fattore, Liana; Fratta, Walter (Frontiers in Behavioral Neuroscience, 2011)
Synthetic cannabinoids are functionally similar to delta9-tetrahydrocannabinol (THC), the psychoactive principle of cannabis, and bind to the same cannabinoid receptors in the brain and peripheral organs. From 2008, synthetic cannabinoids were detected in herbal smoking mixtures sold on websites and in “head shops” under the brand name of Spice Gold, Yucatan Fire, Aroma, and others. Although these products (also known as “Spice drugs” or “legal highs”) do not contain tobacco or cannabis, when smoked they produce effects similar to THC. Intoxication, withdrawal, psychosis and death have been recently reported after consumption, posing difficult social, political and health challenges. More than 140 different Spice products have been identified to date. The ability to induce strong cannabis-like psychoactive effects, along with the fact that they are readily available on the Internet, still legal in many countries, marketed as natural safe substances, and undetectable by conventional drug screening tests, has rendered these drugs very popular and particularly appealing to young and drug-naïve individuals seeking new experiences. An escalating number of compounds with cannabinoid receptor activity are currently being found as ingredients of Spice, of which almost nothing is known in terms of pharmacology, toxicology and safety. Since legislation started to control the synthetic cannabinoids identified in these herbal mixtures, many new analogs have appeared on the market. New cannabimimetic compounds are likely to be synthesized in the near future to replace banned synthetic cannabinoids, leading to a “dog chasing its tail” situation. Spice smokers are exposed to drugs that are extremely variable in composition and potency, and are at risk of serious, if not lethal, outcomes. Social and health professionals should maintain a high degree of alertness for Spice use and its possible psychiatric effects in vulnerable people.